Study of the Communication Strategies Used by Iraqi EFL Students - Ugla, Raed Latif; Adnan, Nur Ilianis; Zainol Abidin, Mohamad Jafre (Institute of Advanced Engineering and Science, 2013)
This study investigates the kinds of communication strategies (CSs) used by Iraqi EFL students. The data analysed in this study were collected in Baghdad University. The study was quantitative in nature where a questionnaire adopted from Dornyei and Scott’s taxonomy of CSs (1995). This questionnaire was used to elicit the findings. The subject consisted of fifty Iraqi EFL students. The results obtained show different kinds of CSs used by Iraqi EFL students. The pedagogical and recommendations were provided in this study.DOI: http://dx.doi.org/10.11591/ijere.v2i1.1812